2020
DOI: 10.1002/iub.2352
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐1224‐5p acts as a tumor suppressor via inhibiting the malignancy of rectal cancer through targeting SLC29A3

Abstract: The emphasis of our study was to determine the physiological function of miR‐1224‐5p in rectal cancer (RC) and its in‐depth mechanism. First, the expression of miR‐1224‐5p in RC tissues was analyzed using public data from the TCGA database. Then, miR‐1224‐5p expression in RC cell lines SW480 and SW837 was measured using the qRT‐PCR assay. The subsequent CCK‐8 assay was executed to assess the function of miR‐1224‐5p in the viability of the RC cell. Bioinformatics prediction prompted that SLC29A3 may be a potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Li et al have already indicated that miR-1224-5p expression was decreased in CRC patients, and its mimic repressed CRC cell metastasis [ 21 ]. Song et al also showed miR-1224-5p suppressed cell proliferation, migration and invasion in CRC [ 33 ]. In this research, it was found that miR-1224-5p expression was significantly downregulated in CRC tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al have already indicated that miR-1224-5p expression was decreased in CRC patients, and its mimic repressed CRC cell metastasis [ 21 ]. Song et al also showed miR-1224-5p suppressed cell proliferation, migration and invasion in CRC [ 33 ]. In this research, it was found that miR-1224-5p expression was significantly downregulated in CRC tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“…We identified that IGFL2-AS1 could interact with miR-1224-5p in TSCC cells. It has been reported that miR-1224-5p acts as a tumor suppressor in many cancers, such as glioma (Qian et al, 2015), ovarian cancer (Wang et al, 2020) and rectal cancer (Song et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We identified that IGFL2‐AS1 could interact with miR‐1224‐5p in TSCC cells. It has been reported that miR‐1224‐5p acts as a tumor suppressor in many cancers, such as glioma (Qian et al, 2015), ovarian cancer (Wang et al, 2020) and rectal cancer (Song et al, 2020). Similarly, our study found that miR‐1224‐5p was lowly expressed in TSCC cells, suggesting that miR‐1224‐5p might exert tumor suppressing function in TSCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous microRNAs (miRNAs) have been identified as vital regulators in human cancers [ 40 ]. MiR-1224-5p played an anti-cancer role in various cancers, such as rectal cancer [ 41 ], pancreatic cancer [ 42 ], ovarian cancer [ 43 ], and glioma [ 44 ]. In addition, a report from Shi et al also elucidated that miR-1224-5p could impair the development of esophageal squamous cell carcinoma, which is another HNSC subtype [ 45 ].…”
Section: Discussionmentioning
confidence: 99%